Upaya Pembentukan Karakter Sopan Santun Bagi Siswa Sekolah Dasar - Aldri Frinaldi; Deliza Syiva Salsabila Nursyam; Ruswanti; Aufa Sadina Ayu; Latifa Azahra (LKP KARYA PRIMA KURSUS, 2025)
This study describes efforts to develop polite character among elementary school students through the involvement of Community Service Program (KKN) students from Universitas Negeri Padang in Nagari Tigo Jangko, Tanah Datar Regency. The study is motivated by the decline in children’s polite behavior influenced by digital media exposure, limited parental supervision, and the lack of moral habituation in schools. A qualitative descriptive approach was used, employing participatory observation, in-depth interviews, and documentation. The findings indicate that KKN students served as role models and catalysts for change through daily habituation, polite communication practices, educational games, and outreach to teachers and parents. Participatory observations revealed improvements in students’ polite behavior, including taking turns, using greetings and expressions of gratitude, and reduced use of inappropriate language. Collaboration among KKN students, teachers, parents, and the local community strengthened the character development process, enabling students to internalize polite values more effectively. This study concludes that contextual and consistent interventions can enhance polite behavior among elementary school children. Keywords: KKN students, politeness, student character, character education